ANALISIS PENGARUH SUHU CAMPURAN AC-WC TERHADAP BERAT JENIS PEKERJAAN JALAN TANIWEL-SALEMAN PULAU SERAM - Rumbia, Najar; Huwae, David Daniel Marthin; Talakua, Elisabeth (Journal Agregate, 2023)
This condition causes the asphalt mixture to be unable to be overlaid on the road work site because the temperature of the mixture is below the overlay and compaction temperature. According to the provisions of the asphalt mixture that has experienced a decrease in temperature can no loger be used. But the reality that happens a lot in the field is that sanding is still done and followed by the next stage, namely compaction. Therefore, it is necessary to conduct research on the effect of heating on the concrete asphalt layer mixture, namely hot rolled sheet-Base (HRS-Base). The method used, the effect of AC-WC asphalt mixture temperature on the specific gravity of road work is . From yhe results of the marshall analysis, the value of marshall parameters that meet the requirements is in the range of asphalt content 4.50-5.80 so that the optimum asphalt content is obtained at the middle value of the limit range above is 5.12%. Comparison of asphalt temperature to field temperature and lab asphalt temperature. The asphalt temperature in the lab is 5.5% asphalt content and the asphalt temperature used in the lab is 160°C, 150°C, 140°C, 130°C, while the asphalt content used in the field is 5.0% asphalt content and the asphalt temperature used in the field is 125°C, 135°C, 140°C, 145°C. Further research needs to be carried out in the form of marshall soaking tests with the intention of measuring the durability of the binding/adhesion of asphalt mixtures to the influence of temperature.